Case report: Carcinosarcoma of uterus in nulliparous women - Sun, Feiyue; Li, Xuelei; Kang, Luyao; Wang, Yiran; Li, Hongyu; Zhu, Hai (Frontiers in Oncology, 2024)
BackgroundUterine carcinosarcoma (UCS), or malignant mixed Müllerian tumor, is a cancer that include both carcinomatous and sarcomatous components, resembling endometrial carcinoma. A 55-year-old woman was admitted to the hospital with postmenopausal vaginal bleeding. Gross examination of the specimen revealed brittle tissue in the fundus and the left wall of the endometrium. Postoperative pathology revealed a mixture of well-differentiated endometrioid adenocarcinoma and osteosarcoma. The patient was never given birth, which may be relevant to the diagnosis. Literature review suggests that being nulliparous may be a significant risk factor for developing uterine carcinosarcoma.Case descriptionIn December 2023, a 55-year-old female patient was admitted to the hospital with postmenopausal vaginal bleeding. Hysteroscopic surgery was performed, and the postoperative pathology showed endometrial cancer accompanied by ossified tissue with necrosis. The immunohistochemical results indicated positive Estrogen receptors (ER), positive Progesterone receptors (PR), ki67 positivity at 70%, negative PTEN, mutated positive p53, focal positive Pax-8, positive SATB2, positive Cytokeratin 7 (CK7), positive EMA and positive Vimentin (Vim). The patient was diagnosed with Uterine carcinosarcoma. On December 18, 2023, the patient underwent partial vaginal resection, bilateral salpingo-oophorectomy, pelvic lymph node dissection, and a sub-extensive laparoscopic hysterectomy. Postoperatively, the patients received radiotherapy and four cycles of chemotherapy in the DC regimen. As of July 2024, laboratory and impact test results showed no tumor recurrence. The patient’s disease-free survival (DFS) was seven months.ConclusionThe rate of childless in patients with uterine carcinosarcoma is at a high level.